MEMBANGUN KONSEP URBAN FARMING DI WISATA UMBUL HELAU SEBAGAI BENTUK EDUKASI KEPADA MASYARAKAT - Carolina, Thabita; Sundari, Susanti; Rahmawati, Desy; Sari, Indah Purnama (Universitas Esa Unggul, 2022)
The PKM Team at Tulang Bawang University Lampung together with partners from Umbul Helau tourism developed the concept of urban farming with aquaponic technology where hydroponic plant cultivation with integrated fish cultivation in the form of budikdamber (budidaya ikan dalam ember) or fish cultivation in buckets. This is proper to do in this tourism because the concept is an educational park. This activity is carried out with the aim of introducing the concept of urban farming that can educate and benefit the wider community. The method used goes through stages starting from determining the time of activities and division of tasks, providing materials, preparing land, preparing cultivation of damber media, distributing seeds, controlling and evaluating. The results that have been obtained are very encouraging where the kangkung plant has been harvested and with packaging can be sold and has economic value, while catfish is growing and will be harvested in the near future. The form of education that has been given to the community in this case Elementary School (SD), both students and teachers are introduced to the concept of urban farming which attracts their interest and enthusiasm because there is new knowledge gained.